Basic Treatment Models for Adult Sexual Offenders - Stojanović, Marija (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
Sexual delinquency is a worldwide problem that affects people of all social and cultural backgrounds, leaving many detrimental consequences for direct and indirect victims as well as the community. The socio-political reaction to sexual offending has changed throughout history. The initial reaction involved an extremely retributive approach, but the development and humanization of society forced the focus of treatment to expand to foster positive potential in the offender's personality and behavior. The main objective of this paper is to present the basic models of treating sex offenders that are supported by research: the Relapse Prevention Model, the Self-Regulation Model, the Risk-Need-Responsivity Model, and the Good Lives Model. The paper will also discuss the incidence of sexual delinquency in Serbia, as well as current findings in the field of sex offender assessment.